HUBUNGAN SANITASI LINGKUNGAN DAN FAKTOR BUDAYA DENGAN KEJADIAN TIFUS DI WILAYAH KERJA PUSKESMAS LAMBUR KABUPATEN TANJUNG JABUNG TIMUR TAHUN 2013. - Ahmad Dahlan; Akhsin Munawar; Supriadi - (Universitas Batanghari Jambi, 2014)
Predictable there are 22 million cases with 200.000 death every year in the whole world. The typhoid prognosis depends on age factor and the body protection (immune status) suffers. The mortality number of typhoid disease increases as the growing age of the sufferers beginning at the age of 30 (thirty). According to Hernawati, from 2005 till 2007, there is an increasing numbers of 32,5 % or 39.562 abdorminalis typhoid cases, and more than 10 % of death caused by the late of diagnosis, treatment and the cure. Typhoid or famous with “tipus” is an infection caused by Salmonella typhi bacterium and Salmonella paratyphi. The typhoid sufferers will have high fever, dizzy, lackness of eating desire, until diarea.The purpose of this research is to know the relationship of environment sanitation, (the waste water line, the clean pure water and the have of water closed) and the culture factors (the use of drinking water, the habit of defecation , the habit of washing hands using soap with the typhoid at Lambur Village Muara Sabak District East Tanjung Jabung area 2013. The design that used is cross sectional the datas analysis consist of univariat analisys, which is bivariat uses chi-square.The result of the research It shows a useful relationship, the having of SPAL with the typhoid cases shows OR as 0,550, p-value 0,033, the have of latrine OR as 0,153 and p value 0,000, the habit of using drinking raw water OR 0,447 p value 0,020, the habit of washing hands with soaps OR 0,381 p value 0,000, the habit of washing hands after defecation OR 0,493 and p value 0,013 with the Typhoid cases at the working area of Lambur (Citizen health center).The suggestions to the Health Service and the cross sector involved, as to increase the health promotion about the ordered typhoid cases continually and including the whole in society. Besides, it is suggested to do efforts socializing PHBS and sanitation accommodation especially latrine, the use of clean water, the habit of washing hands using soaps before eating and after defecation.Key words : SPAL, clean water sources, latrine, the use of drinking water, the habit of washing hands with soap and typhoid cases.